Thalamic oscillatory activity may predict response to deep brain stimulation of the anterior nuclei of the thalamus. (23rd March 2021) - Deutschová, Barbora; Klimeš, Petr; Jordan, Zsofia; Jurák, Pavel; Erőss, Lorand; Lamoš, Martin; Halámek, Josef; Daniel, Pavel; Rektor, Ivan; Fabo, Daniel
Abstract: We hypothesized that local/regional properties of stimulated structure/circuitry contribute to the effect of deep brain stimulation (DBS). We analyzed intracerebral electroencephalographic (EEG) recordings from externalized DBS electrodes targeted bilaterally in the anterior nuclei of the thalamus (ANT) in 12 patients (six responders, six nonresponders) with more than 1 year of follow‐up care. In the bipolar local field potentials of the EEG, spectral power (PW) and power spectral entropy (PSE) were calculated in the passbands 1–4, 4–8, 8–12, 12–20, 20–45, 65–80, 80–200 and 200–500 Hz. The most significant differences between responders and nonresponders were observed in the BRIDGE area (bipolar recordings with one contact within the ANT and the second contact in adjacent tissue). In responders, PW was significantly decreased in the frequency bands of 65–80, 80–200, and 200–500 Hz ( p  < .05); PSE was significantly increased in all frequency bands ( p  < .05) except for 200–500 Hz ( p  = .06). The local EEG characteristics of ANT recorded after implantation may play a significant role in DBS response prediction.